2022
DOI: 10.3389/fenvs.2022.1025027
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on numerical simulation based on CALPUFF and wind tunnel simulation of hazardous chemical leakage accidents

Abstract: CALPUFF, as a Lagrangian puff modeling system, is mostly used in the field of atmospheric environment research and risk assessment. CALPUFF performs well for short-term and short-range release scenarios over complex terrain, as well as long-term and long-range transportation. Therefore, this article uses the CALPUFF model to simulate a toxic gas leakage accident in a hazardous chemical plant in an urban area, focusing on the influence of local buildings. Wind tunnel experiments are performed in accordance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies have shown that the CAL-PUFF model, a Lagrangian-Gaussian plume model, has higher computational accuracy and is more suitable for large-scale spatial pollution impact analysis and prediction (greater than 50 km). In comparison, AERMOD is a steady-state plume model that is more suitable for pollution impact analysis and forecast in medium to small spatial ranges (less than 50 km) (Li et al, 2020;Xu et al, 2022;Zhang et al, 2022;Zhao & Li, 2018). Additionally, the CALPUFF model considers various factors, such as complex terrain and meteorological parameters, which results in more reasonable simulation results for sudden changes in wind direction and improved handling of calm wind conditions compared to the AERMOD model.…”
Section: Calpuff and Wrfmentioning
confidence: 99%
“…Studies have shown that the CAL-PUFF model, a Lagrangian-Gaussian plume model, has higher computational accuracy and is more suitable for large-scale spatial pollution impact analysis and prediction (greater than 50 km). In comparison, AERMOD is a steady-state plume model that is more suitable for pollution impact analysis and forecast in medium to small spatial ranges (less than 50 km) (Li et al, 2020;Xu et al, 2022;Zhang et al, 2022;Zhao & Li, 2018). Additionally, the CALPUFF model considers various factors, such as complex terrain and meteorological parameters, which results in more reasonable simulation results for sudden changes in wind direction and improved handling of calm wind conditions compared to the AERMOD model.…”
Section: Calpuff and Wrfmentioning
confidence: 99%